Development and psychometric validation of a volleyball skill assessment instrument for children aged 10-13 years - Sumantri, Ajis; Ertanto, Dody; Apriansyah, Dolly (UIR Press, 2026)
Background: Existing volleyball skill assessment tools are commonly adapted from adolescent or adult performance standards and may not accurately represent the motor development characteristics of children aged 10-13 years. Moreover, psychometrically validated instruments specifically designed for elementary school students remain limited. Objectives: The objective of this research is to create and test a volleyball skill assessment tool tailored for elementary school pupils aged 10 to 13 years. Methods: The study employed a research and development (R&D) design adapted from the Borg and Gall model. Test building concepts served as the basis for a research and development strategy. Five fundamental volleyball abilities were evaluated by the test: smash, underhand passing, overhand passing, underhand serving, and overhand service. Purposive sampling was used to pick 50 Bengkulu City primary school pupils as participants. Aiken’s V and CVR were used to assess content validity with six experts. Data processing utilised G*Power (v3. 1.9.7) and Jamovi (v2.3.2). Results: Strong content validity was shown by every skill component (CVR > 0.83; Aiken's V ≥ 0.87). EFA identified a two-factor structure that explained 71.84% of the overall variance: offensive technical ability and basic ball control. There were moderate to high relationships between criterion validity and game performance (r = 0.63-0.71). All subtests had strong reliability indices (ICC = 0.87-0.94; test–retest r = 0.79-0.86). Conclusion: The developed instrument demonstrated satisfactory validity and reliability and shows potential for assessing basic volleyball skills among elementary school students. The constraints include a limited sample size and a restricted geographical scope. Future studies should encompass larger, more diverse groups and investigate technology-based evaluation formats to improve applicability.